INTERNALIZING CLIMATE ADAPTATION INTO REGIONAL DEVELOPMENT: A REFLECTION BETWEEN MILITANT HOPE AND ACTION (Interdisciplinary Studies Journal, 2026)
Public managers confronted with the impacts of climate change often justify inaction by claiming that it is a “new and controversial” issue. In this essay, we argue that two peripheral intellectuals in the field of regional development studies, Celso Furtado and Chico Mendes, already pointed out in the 1970s the limits of economic growth and advocated development models with a transition to greater social justice and sustainability, even though these terms were not yet in use. We argue that Celso Furtado, one of the leading theorists in the study of regional development in Brazil, was ahead of his time when, in 1972, he identified global warming as a challenge to development. We ask: Were there areas of perception that Furtado did not recognize when he wrote his essay “Structural Trends in the Capitalist System in the Phase of Large Company Predominance”? Using the framework established by Furtado, we expand the reflection to present an empirical case of regional development that, over two decades, promoted a transition to more sustainable development in Acre. We conclude the essay by seeking inspiration in the actions initiated by Chico Mendes to highlight how much this intellectual was also ahead of his time and remains relevant in the debate on the territorial basis of climate adaptation.
Keywords: Global Warming; Territorial Adaptation; Quality of Life